Pengembangan Media Pembelajaran Video Kelas III Tema 6 “Energi & Perubahannya” di Sekolah Dasar - Danik Jelita Mar'atus Sholikah; Masithoh, Dewi (EDUPEDIA Publisher, 2022)
This study aims to produce video products as a science learning medium that is suitable for use in grade III students in elementary school. This research is Research and Development (R&D), with the development stage using the ADDIE model, which consists of 5 stages, including: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The study was conducted from January to June 2022. The subject of the study was a grade III student at MI Ma'arif Serut, Bantul. Data collection techniques use questionnaires. Analyze data using Microsoft Excel. The results showed that learning video media is suitable for use in learning science competencies based on assessments from material experts and media experts, with a score of 4.08 in the